Crustal Cracks and Frozen Flow in Oceanic Lithosphere Inferred From Electrical Anisotropy. (10th December 2019) - Chesley, Christine; Key, Kerry; Constable, Steven; Behrens, James; MacGregor, Lucy
Abstract: Geophysical observations of anisotropy in oceanic lithosphere offer insight into the formation and evolution of tectonic plates. Seismic anisotropy is well studied but electrical anisotropy remains poorly understood, especially in the crust and uppermost mantle. Here we characterize electrical anisotropy in 33 Ma Pacific lithosphere using controlled‐source electromagnetic data that are highly sensitive to lithospheric azimuthal anisotropy. Our data reveal that the crust is ∼18–36 times more conductive in the paleo mid‐ocean ridge direction than the perpendicular paleo‐spreading direction, while in the uppermost mantle conductivity is ∼29 times higher in the paleo‐spreading direction. We propose that the crustal anisotropy results from subvertical porosity created by ridge‐parallel normal faulting during extension of the young crust and thermal stress‐driven cracking from cooling of mature crust. The magnitude of uppermost mantle anisotropy is consistent with recent experimental results showing strong electrical anisotropy in sheared olivine, suggesting its paleo‐spreading orientation results from sub‐Moho mantle shearing during plate formation. Plain Language Summary: A major goal in geoscience is to understand the creation and evolution of oceanic lithosphere. To that end, geophysicists study how properties like electrical conductivity vary with direction and depth in the oceanic lithosphere. We call such directional variation "electrical anisotropy." Since electrical conductivity is particularly sensitive to fluids, certain minerals, and past deformation, the patterns of electrical anisotropy in the crust and mantle provide evidence for how the lithosphere forms and evolves. For the first time, we use an active‐source electromagnetic technique to constrain the electrical anisotropy of Pacific oceanic crust and the shallowest portions of the mantle. Our model shows that the oceanic crust and uppermost mantle are highly anisotropic. We interpret the electrical anisotropy in the crust as fluid‐filled cracks that parallel the paleo mid‐ocean ridge. This suggests that crustal electrical structure begins to form at the mid‐ocean ridge and continues to evolve over time through those early weaknesses. If such cracks are also present in other tectonic plates, then the oceanic crust may be a more important reservoir of water than previously thought. Uppermost mantle electrical anisotropy is consistent with strong shear deformation of olivine that freezes into the mantle early in its formation. Key Points: The oceanic crust and uppermost mantle both exhibit azimuthal electrical anisotropy, but with maximum conductivity in different directions The crust is about 18–36 times more conductive in the vertical plane aligned with the paleo‐ridge axis, suggesting fluids in cracks An uppermost mantle that is about 29 times more conductive in the paleo‐spreading direction is consistent with shearing of olivine at the MOR